Academic Burnout Among College Students in the Digital Age: An Educational Psychology Review - Risalatul Kamila; Ellen Prima (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid expansion of digital technology has fundamentally transformed learning practices in higher education, creating new opportunities for flexibility, accessibility, and academic engagement while simultaneously introducing complex psychological challenges for students. One of the most significant concerns is academic burnout, a condition characterized by emotional exhaustion, cynicism toward academic activities, and reduced academic efficacy resulting from prolonged exposure to academic stressors. This study aims to examine the phenomenon of academic burnout among college students in the digital age through the lens of educational psychology. Employing a qualitative literature review design, the study synthesizes findings from peer-reviewed journal articles, scholarly books, and relevant academic publications addressing the antecedents, consequences, and intervention strategies associated with academic burnout. The findings indicate that excessive academic workload, technostress, intensive social media use, poor self-regulation, ineffective time management, and limited social support are major factors contributing to burnout. The condition negatively affects students’ mental health, academic motivation, learning engagement, and academic performance. From an educational psychology perspective, preventive efforts should emphasize self-regulated learning, effective time-management skills, social support enhancement, and student well-being-oriented learning environments. These findings highlight the importance of holistic educational approaches to support academic success and psychological well-being in digitally mediated higher education contexts.